Power, approach, and inhibition: empirical advances of a theory. (June 2020) - Cho, Minha; Keltner, Dacher
Abstract : The approach-inhibition theory of power proposed that elevated power (which relates to increased rewards and freedom) activates approach-related tendencies, whereas reduced power (which relates to increased threat, punishment, and social constraint) activates inhibition-related tendencies Keltner et al. (2003). In the current article, we review the empirical advances — over the past 16 years — regarding four main propositions of the approach-inhibition theory of power: (a) positive affect versus negative affect, (b) attention to rewards versus attention to threats, (c) automatic cognition versus systematic/controlled cognition, and (d) disinhibited and state/trait driven behavior versus inhibited and situationally constrained behavior. By revealing robust empirical support for, and imaginative extensions of, the four propositions, this review invites future studies of power to further build upon and revise the early claims of approach-inhibition theory.